INDICATORS OF EFFICIENCY OF THE PILOTLESS AVIATION COMPLEX - A. S. Benkafo (Системный анализ и прикладная информатика)
The general principles of an estimation of efficiency of application of pilotless aviation complexes are considered at monitoring of a terrestrial surface in the conditions of presence of unauthenticity of the information on the basis of mathematical  modelling  with  the  account  of  hierarchical  construction  and  influence of  the  human  factor.  The substantiation of indicators of efficiency of information system and likelihood characteristics of an estimation of the information necessary for decision-making is spent.